A triboelectric nanogenerator implemented with an acoustic foam for a self-driven silent tire. (1st June 2022) - Kim, Weon-Guk; Kim, Jin-Ki; Kim, Do-Wan; Tcho, Il-Woong; Choi, Yang-Kyu
Abstract: As autonomous vehicles are rapidly developing, the required electrical energy for operating various in-tire sensors as well as in-vehicle sensors is also increasing. In addition, noise from tires is becoming a critical issue given that the growth of electric vehicles eliminates the noise from engines. Thus, we develop a triboelectric nanogenerator implemented inside a tire with an acoustic foam for a self-driven silent tire, abbreviated as Tire-TENG. The manufactured Tire-TENG maintains the sound absorption ability of pristine acoustic foam while generating electrical energy using the radial acceleration change of a tire. In a laboratory test, the Tire-TENG with a volume of 50 mm × 50 mm × 30 mm shows power of 3.38 mW. As an actual application, six Tire-TENGs with each volume of 120 mm × 110 mm × 30 mm are mounted at the inner surface of a tire. At a speed of 100 km/h and with a weight load of 3500 N, 40 light-emitting diodes were lit bright enough to be seen in a daylight environment without any extra power source. By virtue of its high output characteristics, the Tire-TENG showed feasibility as a self-driven and sound-attenuated in-tire solution thus far not yet reported. Graphical Abstract: ga1 Highlights: A triboelectric nanogenerator (Tire-TENG) was implemented with an acoustic foam utilized for a silent tire. The manufactured Tire-TENG maintains the sound absorption ability of pristine acoustic foam while generating electrical energy using the radial acceleration change of a tire. In a laboratory test, the Tire-TENG with a volume of 5 cm × 5 cm × 3 cm shows power of 3.38 mW. In the flat-trac test, 40 light-emitting diodes were lit bright enough to be seen in a daylight environment by the Tire-TENG with total volume of 12 cm × 66 cm × 3 cm.